ANALISIS PENERAPAN UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY TERHADAP NIAT MENGGUNAKAN QRIS: (Studi Pada Generasi X Di Kabupaten Kendal) - Fauziah, Annisa Fitri; Apriliyanto, Nanang (STIE Mahardhika, 2025)
Technological advances in the payment system have replaced the role of cash into a more efficient and economical form of non-cash payment. Bank Indonesia released a Quick Response (QR) Code standard for payments through server-based electronic money applications, electronic wallets, or mobile banking called the QR Code Indonesian Standard (QRIS). This study aims to determine the factors that influence behavioral intention to use QRIS by using Unified Theory of Acceptance and Use Technology (UTAUT) theory model. This study explores the Generation X in Kendal Regency, Central Java, Indonesia. The research method used quantitative method with 160 samples of Generation X in Kendal Regency, Central Java and used Smart PLS version 3.0. for analyze the data. The results of this study show Performance Expectancy, Effort Expectancy, and Social Influence has a positive and significant impact on Behavioral Intention the use of QRIS for Generation X in Kendal Regency, Central Java.